2022
DOI: 10.5114/ain.2022.118095
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the use of stimulants and sedatives by secondary school students

Abstract: No ghostwriting and guest authorship declared./Nie występują zjawiska ghostwriting i guest authorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This may be related to alcohol consumption, which is known to be a predictor of other drugs usage (for example nicotine). A reduced number of occasions to drink alcohol (during lockdown) could entail a small decrease in psychostimulants or cannabinoids [ 24 ]. It can also be suggested that in the early days of the pandemic, the supply chains of psychoactive drugs may have been disrupted and their availability reduced.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to alcohol consumption, which is known to be a predictor of other drugs usage (for example nicotine). A reduced number of occasions to drink alcohol (during lockdown) could entail a small decrease in psychostimulants or cannabinoids [ 24 ]. It can also be suggested that in the early days of the pandemic, the supply chains of psychoactive drugs may have been disrupted and their availability reduced.…”
Section: Discussionmentioning
confidence: 99%